2017
DOI: 10.2147/copd.s147968
|View full text |Cite
|
Sign up to set email alerts
|

Trends in health care resource utilization and pharmacological management of COPD in Taiwan from 2004 to 2010

Abstract: RationaleCOPD has attracted widespread attention worldwide. The prevalence of COPD in Taiwan has been reported, but little is known about trends in health care resource utilization and pharmacologic management in COPD treatment.ObjectiveThe objective of this article was to study trends in health care resource utilization, pharmacologic management, and medical costs of COPD treatment in Taiwan.Materials and methodsReimbursement claims in the Taiwan National Health Insurance System from 2004 to 2010 were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Furthermore, ICS and OS formula may attenuate the risk of hepatic, renal, and heart failure. In agreement with our result, Tsai et al discovered that the ICS formula was associated with the lowest frequency of ICU admission based on the NHIRD (Tsai et al, 2017). Statin use in the early course of ACO may attenuate these risks in the later course of this disease.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, ICS and OS formula may attenuate the risk of hepatic, renal, and heart failure. In agreement with our result, Tsai et al discovered that the ICS formula was associated with the lowest frequency of ICU admission based on the NHIRD (Tsai et al, 2017). Statin use in the early course of ACO may attenuate these risks in the later course of this disease.…”
Section: Discussionsupporting
confidence: 93%
“…Tsai et al found that the average number of hospital and ICU admissions mainly affected the average total medical cost at the end of life in COPD patients. 42 In particular, a hospital admission for a COPD exacerbation episode that requires intensive care represents a significant milestone that may merit advanced care planning and may be an opportunity to initiate communication on end-of-life care. The care model should consider the specific cost trend of COPD and integrate palliative care during the lifelong disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily Tsai et al [32] found a 12.4% decrease of direct costs from US$3434 in 2004 to US$3008 in 2010 in Taiwan, mainly attributable to decreased average numbers of hospital and intensive care unit admissions. Also for the US Nurmagambetov et al [33] measured direct costs for COPD in a working age patients and found a decline in expenditures from US$1400 in 1999 to US$960 in 2003 in varying populations, which is mainly attributable to a reduction in hospital admissions.…”
Section: Discussionmentioning
confidence: 99%